1966
DOI: 10.1021/jf60144a006
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Activator, Penetration and Distribution Studies in Bean, Cotton, and Barley from Foliar and Root Applications of Tween 20-C14-Fatty Acid and Oxyethylene Labeled

Abstract: Evidence from column, paper, and thin-layer chromatography indicates that Tween 20 is a mixture of numerous compounds. Carbon-14 distribution patterns in bean, barley, and cotton were determined following foliar and root applications of Tween 20-C14 (oxyethyiene and fatty acid labeled), and of fractions of both materials eluted from a CM Sephadex column. Marked differences existed between the oxyethyiene and fatty acid labeled surfactants with respect to the distribution of C14 in the plants from either root o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1971
1971
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…which have both surfactant and humectant properties. This class of surfactant is known to be poorly taken up by leaves (Smith & Foy, 1966;McWhorter, 1985;Sugimura & Takeno, 1985), and consequently any enhancement effects produced can only be by interaction with the herbicide deposited on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…which have both surfactant and humectant properties. This class of surfactant is known to be poorly taken up by leaves (Smith & Foy, 1966;McWhorter, 1985;Sugimura & Takeno, 1985), and consequently any enhancement effects produced can only be by interaction with the herbicide deposited on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…A good example of this effect is provided by the work of MacIsaac et al ,19 who examined the effect of a 20EO sorbitan monododecanoate (SE20EO) on glyphosate absorption by tartary buckwheat ( Fagopyrum tataricum (L) Gaertn) and concluded that the uptake‐enhancing effect of this additive was probably related to its hygroscopic properties, maintaining the herbicide in a soluble and more available state for cuticular penetration. Earlier studies with radiolabelled surfactants of this class had already indicated that they were unlikely to be taken up by leaves 20. Some data confirming the effectiveness of SE20EO as an adjuvant for glyphosate uptake are given in Table 3 4…”
Section: Processes Involved In Transfer From Spray Tank To Site Of mentioning
confidence: 97%
“…Norris and Freed [48] recovered 90% of the 14 C in the rinse of leaves for black valentine beans (Phaseolus vulgaris) treated with 14 C-Pluronic L-62 (nonionic surfactant). Smith and Foy [49] recovered 30 to 53% of the 14 C at 4 DPT in rinse from leaves of bean plants treated with 14 C-Tween 20.…”
Section: Fate Of Rodeo and X-77 Spreadermentioning
confidence: 99%
“…Black valentine beans (P. vulgaris) treated with 14 C-Pluonic L-62 contained 8% 14 C in treated leaflets at 3 DPT [48]. Smith and Foy [49] found 44 to 69% of 14…”
Section: Fate Of Rodeo and X-77 Spreadermentioning
confidence: 99%